Prevalence of Cattle Trypanosomosis and Apparent Density of Its Fly Vectors in Bambasi District of Benishangul-Gumuz Regional State, Western Ethiopia - Morka Amante; Hika Tesgera (Veterinary Medicine International)
Trypanosomosis is the most serious disease of cattle, which causes great socioeconomic losses in the country. Its socioeconomic impact is reflected on direct losses due to mortality, morbidity, and reduction in milk and meat production, abortion and stillbirth, and also costs associated with combat of the disease are direct losses. A cross-sectional study was carried out to assess the prevalence of cattle trypanosomosis, and the apparent density and distribution of its fly vectors in selected study areas. The methods employed during the study were buffy coat technique for parasitological study and deploying trap for the collection of tsetse flies. A total of 1512 flies were trapped, and among them, 1162 were tsetse flies while 350 were biting flies. Higher apparent density for tsetse fly (7.7 F/T/D) followed by Stomoxys (0.9 F/T/D), Tabanus (0.8 F/T/D), and Hematopota (0.6 F/T/D) was recorded. Out of 638 examined cattle, the overall prevalence of trypanosomosis in the study area was 9.1% (58/638). Out of positive cases, Trypanosoma congolense (7.7%) was the dominant trypanosome species followed by Trypanosoma vivax (0.9%), Trypanosoma brucei (0.2%), and mixed infection of Trypanosoma brucei and Trypanosoma vivax (0.3%). There was no a significant difference (p>0.05) in trypanosome infection between age, sex, and trypanosome species. The prevalence of trypanosomosis on the bases of body condition was 2.8% for poor, 5.5% for medium, and 0.8% for good body condition. The overall prevalence of anemia was (36.8%), and presence of anemia was higher in trypanosome positive animals (62.5%) than in negative animals (34.3%) which is statistically significant (p<0.05, CI = 1.794–5.471). The overall mean packed cell volume (PCV) value for examined animals was 25.84 ± 0.252SE. Mean (PCV) of parasitaemic cattle (9.1%) was significantly (p<0.05) lower than that of aparasitaemic cattle (90%). This survey showed that trypanosomosis is still a core problem for livestock production of the study area. Therefore, more attention should be given to the control of both the disease and its vectors.